Meningkatkan Kinerja Guru SD Melalui Penelitian Tindakan Sekolah: Pendekatan Kolaboratif untuk Peningkatan Pembelajaran - Chandra Sagul Haratua; Lilis Aenun Zariah; Eva Mulida Hazana; Dian Purnamasari; Ferra Yuliantika Asmara Murni; Lukman Lukman (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This action research aimed to improve the performance of teachers through a collaborative approach at SD Negeri Lulut 2, Klapanunggal, Bogor Regency. The study identified key issues in teacher performance and student learning outcomes, planned collaborative strategies involving teachers, the school principal, students, parents, and other stakeholders. Data were collected through observation, interviews, questionnaires, and documentation, analyzed, and action plans implemented. The findings showed a significant improvement in teacher performance and student learning outcomes, particularly in classes 5 and 6. Collaboration among stakeholders proved essential in achieving these improvements. However, challenges such as resource availability for innovative learning implementation remain. Continuous commitment and collaboration are essential for sustained educational quality improvement.